Electrolyte membrane, secondary battery and electric equipment
By using a polymer membrane embedded with NASCON and a halide ion conductor electrolyte membrane in sodium ion batteries, the problem of dendrite growth in sodium ion batteries was solved, and the cycle stability and electrochemical performance of the battery were improved.
Patent Information
- Application Number
- CN202510841965.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-09-19
AI Technical Summary
In sodium-ion batteries, the potential difference and uneven charge distribution at the contact interface between the metal negative electrode and the electrolyte lead to uneven sodium ion deposition, causing dendrite growth, poor cycle stability and electrolyte decomposition.
A polymer membrane is used as a frame, ion conductors of NASCON and halide ion conductors are embedded, and their mass ratio is controlled. Organic solvents and organic fillers are added to form a gel polymer electrolyte membrane to optimize interface contact and ion migration.
Effectively inhibit dendrite formation, improve battery cycle stability and life, enhance interfacial ion migration kinetics, and enhance electrochemical performance.
Smart Images

Figure CN120674585A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte membrane, a secondary battery, and an electrical device. Background Art
[0002] Energy storage devices, particularly secondary batteries, have undergone decades of research and development. Rechargeable batteries can effectively store renewable energy from solar and wind power. However, commercial lithium-ion batteries require expensive and scarce resources such as lithium and cobalt, which greatly limits their large-scale application in energy storage systems.
[0003] In recent years, sodium-ion batteries (Na-ion batteries) have attracted increasing attention as a promising alternative to lithium-ion batteries due to their high natural abundance and low cost. The sodium metal anode has a high theoretical capacity (1166 mAh / g) and a low redox potential (2.71 V compared to the standard hydrogen potential), resulting in Na-metal batteries with high operating voltages and higher energy densities. Therefore, the development of Na-metal batteries holds great promise and promises high application value for the development of sustainable, high-performance energy storage batteries, such as Na-O2 and Na-S batteries. However, in Na-ion battery systems, the interfacial potential difference between the metal anode and the electrolyte, as well as the uneven charge distribution on the anode surface, lead to uneven deposition and stripping of Na ions on the anode surface, causing dendrite growth. This disrupts the uniform formation of the electrolyte interphase (SEI) film. Furthermore, the repeated repair and rupture of the SEI film leads to the formation of "dead sodium" and the continuous consumption of active Na metal, which in turn exacerbates the decomposition of the electrolyte and results in poor cycling stability. Summary of the Invention
[0004] Therefore, the present application provides an electrolyte membrane, a secondary battery and an electrical device, the purpose of which is to, on the one hand, inhibit the formation of Na dendrites in metal batteries and improve the battery cycle stability and safety; on the other hand, provide good interface performance and electrolyte dynamics, which can improve the rate performance in practical applications.
[0005] To achieve the above object, according to one aspect of the present application, an electrolyte membrane is provided, comprising a polymer membrane, an ion conductive agent, an organic solvent, an organic filler, and a sodium salt, wherein the polymer membrane has pores, and the ion conductive agent, the organic solvent, the organic filler, and the sodium salt are distributed in at least a portion of the pores; the ion conductive agent comprises a NASCON ion conductor and a halide ion conductor;
[0006] The ion conductor satisfies the following relationship: 0.2≤m1 / m2≤1.5; wherein m1 is the mass of the NASCON ion conductor in the electrolyte membrane, and m2 is the mass of the halide ion conductor in the electrolyte membrane.
[0007] Furthermore, the NASCON ion conductor includes at least one of the compounds of the following chemical formula: Na 1+ x Zr 2-y M y Si x-y P 3-x+y O 12 , wherein 0≤x≤3, 0≤y≤1, and M is selected from one or more of Li, Ca, Mg, Sr, Ba, In, Ga, Nb, La, Cr, Mn, Zn, Al, Ge, and Bi;
[0008] The chemical formula of the halide ion conductor is as follows: Na3NX6, wherein N is selected from one or more of Sc, Y, Yb, and In, and X is a halogen.
[0009] Furthermore, the ion conductor also includes a sulfide ion conductor, and the sulfide ion conductor includes Na3Sn2S4, Na3W2S4, Na3Sb2S4, Na 11 Sn2SbS 12 、Na 11 Sn2PS 12 One or more of .
[0010] Furthermore, the ion conductor satisfies the following relationship: 0.2≤m1 / m3≤1; wherein m3 is the mass of the sulfide ion conductor in the electrolyte membrane.
[0011] Further, the sodium salt includes one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(trifluoromethanesulfonyl)imide (NaN(CF3SO2)2), tris(trifluoromethanesulfonyl)methyl sodium (NaC(CF3SO2)3), sodium bis(oxalatoborate) (NaBOB), sodium difluorooxalatoborate (NaODFB), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and sodium difluorophosphate (NaPO2F2); and / or,
[0012] The organic solvent includes one or more of ethyl methyl carbonate, ethylene carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, γ-butyrolactone, ethyl difluoroacetate, dimethyl carbonate, methyl propionate, methyl trifluoroacetate, ethyl propionate, propyl propionate, tetrahydrofuran, 2-methyltetrahydrofuran, ethyl acetate, propyl acetate, difluoroethyl acetate, ethyl trifluoroacetate, and propyl trifluoroacetate; and / or the organic filler includes one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and derivatives thereof.
[0013] Furthermore, at least one of the following conditions is met:
[0014] a. The mass proportion of the ion conductive agent in the electrolyte membrane is 0.5%-20%;
[0015] b. The mass percentage of the sodium salt in the electrolyte membrane is 2% to 16%;
[0016] c. The mass proportion of the organic solvent in the electrolyte membrane is 5% to 45%;
[0017] d. The particle size Dv50 of the ion conductive agent is 0.5 to 30 μm;
[0018] e. The organic filler accounts for 35-56% by mass in the electrolyte membrane.
[0019] Furthermore, at least one of the following conditions is met:
[0020] 1) The thickness of the polymer film is 5 to 50 μm;
[0021] 2) The tensile strength of the polymer film is 48 to 72 MPa;
[0022] 3) The porosity of the polymer film is 15% to 60%.
[0023] Furthermore, at least one of the following conditions is met:
[0024] A. The porosity of the electrolyte membrane is 15% to 70%;
[0025] B. The thickness of the electrolyte membrane is 7 to 55 μm;
[0026] C. The room temperature ionic conductivity of the electrolyte membrane is 2.6×10 -3 ~4.6×10 -3 S / cm.
[0027] According to another aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, and an electrolyte membrane as described above in any one of the present application, wherein the positive electrode sheet comprises a sodium ion transition metal oxide.
[0028] According to another aspect of the present application, an electric device is provided, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.
[0029] The electrolyte membrane of the present application uses a polymer membrane as the frame body, and ion conductors including NASCON ion conductors and halide ion conductors are embedded in the pores of the polymer membrane. The mass ratio of NASCON ion conductors and halide ion conductors is controlled within a certain range. An integrated gel polymer electrolyte membrane formed by adding organic solvents, organic fillers and sodium salts can be well compatible with the positive and negative electrodes to form a good contact interface, promote interface homogenization and rapid and efficient ion migration, can effectively inhibit interfacial side reactions, and improve interfacial ion migration kinetics. In the sodium metal battery system, it can effectively reduce interfacial side reactions and inhibit dendrite formation, thereby improving battery cycle stability and life. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the specific implementation methods or the description of the prior art. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0031] Figure 1 Schematic diagram of the interface between the electrolyte membrane and the electrode;
[0032] Figure numerals: 1, positive electrode; 2, electrolyte membrane; 21, ion conductor; 22, organic filler; 23, polymer membrane; 3, negative electrode. DETAILED DESCRIPTION
[0033] The following will clearly and completely describe the concept and technical effects of this application in conjunction with the embodiments to fully understand the purpose, features and effects of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of them. Based on the embodiments of this application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of this application.
[0034] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0035] In the description of this application, "several" means more than one, "plurality" means more than two, "greater than," "less than," and "exceed" are understood to exclude the number itself, while "above," "below," and "within" are understood to include the number itself. The use of "first" and "second" in the description is solely for the purpose of distinguishing technical features and should not be construed as indicating or implying relative importance, implicitly specifying the number of the indicated technical features, or implicitly specifying the order of the indicated technical features.
[0036] In the description of this application, reference to the terms "one embodiment," "some embodiments," "illustrative embodiments," "examples," "specific examples," or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of this application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any appropriate manner in any one or more embodiments or examples.
[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments is not specified, they are all commercially available conventional reagents.
[0038] Due to the potential difference between the contact interface between the sodium metal negative electrode and the electrolyte, as well as the uneven charge distribution on the surface of the sodium metal negative electrode, sodium metal batteries cause uneven deposition and stripping of sodium ions on the negative electrode surface, which causes dendrite growth and leads to poor cycle stability.
[0039] In a typical embodiment of the present application, an electrolyte membrane is provided, comprising a polymer membrane, an ion conductor, an organic solvent, an organic filler and a sodium salt, wherein the polymer membrane has pores, and the ion conductor, the organic solvent, the organic filler and the sodium salt are distributed in at least a portion of the pores; the ion conductor comprises a NASCON ion conductor and a halide ion conductor, and the ion conductor satisfies the following relationship: 0.2≤m1 / m2≤1.5; wherein m1 is the mass of the NASCON ion conductor in the electrolyte membrane, and m2 is the mass of the halide ion conductor in the electrolyte membrane. By using a polymer membrane as the main frame, ion conductors including NASCON ion conductors and halide ion conductors are embedded in the pores of the polymer membrane, and the mass ratio of NASCON ion conductors to halide ion conductors is controlled within the above range. An integrated gel polymer electrolyte membrane formed by adding organic solvents, organic fillers and sodium salts can be well compatible with the positive and negative electrodes to form a good contact interface, promote interface homogenization and rapid and efficient ion migration, effectively inhibit interfacial side reactions, and improve interfacial ion migration kinetics. In sodium metal battery systems, it can effectively reduce interfacial side reactions and inhibit dendrite formation, thereby improving battery cycle stability and life.
[0040] In some preferred embodiments, the NASCON ion conductor comprises at least one compound of the following chemical formula: Na 1+x Zr 2-y M y Si x-y P 3-x+y O 12 , wherein 0≤x≤3, 0≤y≤1, and M is selected from one or more of Li, Ca, Mg, Sr, Ba, In, Ga, Nb, La, Cr, Mn, Zn, Al, Ge, and Bi. The above-mentioned NASCON ion conductor has excellent air stability and thermal stability.
[0041] The halide ion conductor has the following chemical formula: Na3NX6, where N is selected from one or more of Sc, Y, Yb, and In, and X is a halogen. The halogen is fluorine, chlorine, bromine, or iodine. These halide ion conductors offer high ionic conductivity, are environmentally friendly, have a wide voltage window, and exhibit excellent electrochemical stability. Combined with the exceptional stability of the NASCON ion conductor, they significantly improve the thermal and electrochemical stability of the electrolyte membrane, optimizing the ionic conductivity and enhancing the electrochemical performance of the electrolyte membrane.
[0042] In some preferred embodiments, the ion conductive agent further comprises a sulfide ion conductor, wherein the sulfide ion conductor comprises Na3Sn2S4, Na3W2S4, Na3Sb2S4, Na 11 Sn2SbS12 、Na 11 Sn2PS 12 The sulfide ion conductor has high ionic conductivity and plasticity, which makes the battery interface compatibility better.
[0043] In some preferred embodiments, the ion conductor satisfies the following relationship: 0.2 ≤ m1 / m3 ≤ 1, where m3 is the mass of the sulfide ion conductor in the electrolyte membrane. By controlling the mass ratio of the NASCON ion conductor to the sulfide ion conductor within the above range, the combined effect of the two types of ion conductors can enhance the conductivity of the electrolyte membrane while further improving its stability and strength, optimizing the interfacial contact between the electrolyte and the electrode material, thereby reducing the internal impedance of the battery and enhancing electrochemical performance.
[0044] In some preferred embodiments, the sodium salt includes one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(trifluoromethanesulfonyl)imide (NaN(CF3SO2)2), sodium tris(trifluoromethanesulfonyl)methyl (NaC(CF3SO2)3), sodium bis(oxalatoborate) (NaBOB), sodium difluorooxalatoborate (NaODFB), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and sodium difluorophosphate (NaPO2F2). The addition of the above sodium salts enables the electrolyte membrane to be more compatible with the positive and negative electrodes to form a good contact interface, promotes interface homogenization, fast and efficient ion migration, and improves cycle performance.
[0045] In some preferred embodiments, the organic solvent includes one or more of ethyl methyl carbonate, ethylene carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, γ-butyrolactone, ethyl difluoroacetate, dimethyl carbonate, methyl propionate, methyl trifluoroacetate, ethyl propionate, propyl propionate, tetrahydrofuran, 2-methyltetrahydrofuran, ethyl acetate, propyl acetate, difluoroethyl acetate, ethyl trifluoroacetate, and propyl trifluoroacetate. The addition of the above organic solvents enables the electrolyte membrane to be more compatible with the positive and negative electrodes to form a good contact interface, promotes interface homogenization, fast and efficient ion migration, and improves cycle performance.
[0046] In some preferred embodiments, the organic filler includes one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and their derivatives.
[0047] As used herein, the term "derivative" refers to a similar compound obtained by chemically altering a portion of a compound but having the same or even better properties than the original compound. Thus, derivatives of the polymers of the present invention refer to chemical modifications including the incorporation of various groups, such as aldehyde, amino, carboxylic acid, ketone, amide, ester, sulfate, alkoxy, phosphate, and the like.
[0048] In some preferred embodiments, the ion conductive agent comprises 0.5% to 20% by weight of the electrolyte membrane. Within this range, the ion conductive agent can significantly improve the electrolyte membrane's ion mobility coefficient and electrical conductivity, thereby improving both battery cycle performance and rate capability. For example, the ion conductive agent can comprise 0.5%, 5%, 10%, or 20% by weight of the electrolyte membrane.
[0049] In some preferred embodiments, the sodium salt accounts for 2% to 16% by weight of the electrolyte membrane. This range not only significantly improves the electrolyte membrane's ion mobility and conductivity, but also enhances interfacial compatibility between the electrolyte membrane and the positive and negative electrodes, thereby improving both battery cycle performance and rate capability. For example, the sodium salt may account for 2%, 4%, 8%, 15%, or 16% by weight of the electrolyte membrane.
[0050] In some preferred embodiments, the mass percentage of the organic solvent in the electrolyte membrane is 5% to 45%. The mass percentage of the organic solvent within the above range can not only significantly improve the ion mobility coefficient of the electrolyte membrane and improve the conductivity, but also better promote the interfacial compatibility between the electrolyte membrane and the positive and negative electrodes, thereby improving the battery cycle performance and the battery rate performance. For example, the mass percentage of the sodium salt in the electrolyte membrane can be 0.5%, 1%, 5%, 25%, or 45%.
[0051] In some preferred embodiments, the particle size Dv50 of the ion conductive agent is 0.5 to 30 μm. Using an ion conductive agent within this particle size range can facilitate greater embedding of the ion conductive agent into the polymer membrane, reduce the transport path of sodium ions, and thereby increase the ion mobility coefficient and improve conductivity. For example, the particle size Dv50 of the ion conductive agent can be 0.5 μm, 5.0 μm, 10.0 μm, 20.0 μm, or 30.0 μm.
[0052] In some preferred embodiments, the organic filler accounts for 35-56% by weight of the electrolyte membrane. This range not only helps evenly disperse and fix the ion conductors in the electrolyte membrane, but also maintains uniform absorption of the solvent and sodium salt by the electrolyte membrane, thereby ensuring good ionic conductivity of the electrolyte membrane. For example, the organic filler can account for 35%, 39.7%, 45.2%, 46.1%, 47.1%, 47.8%, 48.2%, 49.1%, 50.1%, 52.2%, 53.3%, or 56% by weight of the electrolyte membrane.
[0053] In some preferred embodiments, the polymer film has a thickness of 5 to 50 μm. Polymer films within this thickness range form good interfacial contact with the positive and negative electrodes, significantly increasing the ion mobility coefficient and thereby improving electrical conductivity. For example, the polymer film can have a thickness of 5 μm, 10 μm, 20 μm, or 50 μm.
[0054] In some preferred embodiments, the polymer film has a tensile strength of 48 to 72 MPa. The tensile strength of the polymer film within the above range indicates that the polymer film has excellent mechanical properties. For example, the tensile strength of the polymer film can be 48 MPa, 48.5 MPa, 60.5 MPa, 63.1 MPa, 70.9 MPa, 72 MPa, etc.
[0055] In some preferred embodiments, the polymer membrane has a porosity of 15% to 60%. Polymer membranes within this porosity range form good interfacial contact with the positive and negative electrodes, significantly increasing the ion mobility coefficient and, therefore, improving electrical conductivity. For example, the polymer membrane porosity can be 15%, 30.3%, 45.2%, 59.8%, or 60%.
[0056] In some preferred embodiments, the porosity of the electrolyte membrane is 15% to 70%. Controlling the porosity of the electrolyte membrane within the above range can significantly increase the ion mobility coefficient, thereby improving the conductivity. For example, the porosity of the electrolyte membrane can be 15%, 16.2%, 31.9%, 36.2%, 37.0%, 38.2%, 39.1%, 40.2%, 41.0%, 43.1%, 47.3%, 48.2%, 66.5% or 70%, etc.
[0057] In some preferred embodiments, the thickness of the electrolyte membrane is 7 to 55 μm. Controlling the thickness of the electrolyte membrane within this range can significantly increase the ion mobility coefficient, thereby improving the conductivity. For example, the thickness of the electrolyte membrane can be 7 μm, 11.0 μm, 12.1 μm, 13.2 μm, 14.2 μm, 26.3 μm, 38.2 μm, or 55 μm.
[0058] In some preferred embodiments, the room temperature ionic conductivity of the electrolyte membrane is 2.6×10 -3 ~4.6×10 -3 S / cm. Controlling the room temperature ionic conductivity of the electrolyte membrane within the above range can significantly improve the discharge capacity and rate performance of the battery. For example, the room temperature ionic conductivity of the electrolyte membrane can be 2.6×10 -3 , 3×10 -3 S / cm, 3.34×10 -3 S / cm, 4.14×10 -3 S / cm or 4.6×10 -3 wait.
[0059] In some preferred embodiments, the polymer membrane is mainly prepared by polymerizing a high molecular weight polymer and then undergoing an electrospinning process, wherein the high molecular weight polymer includes one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and their derivatives.
[0060] In some preferred embodiments, the high molecular weight polymer is dissolved in a conventional solvent prior to electrospinning to prepare an electrospinning solution having a concentration of 5 to 20 wt %. The solvent comprises one or more of N,N-dimethylformamide (DMF) and N-methylpyrrolidone.
[0061] In some preferred embodiments, electrospinning is followed by calcination to form a polymer membrane at a temperature of 150-300° C. for 1-10 h.
[0062] In some preferred embodiments, the method for preparing the electrolyte membrane comprises immersing a polymer membrane in a liquid containing an ion conductive agent, drying it for the first time, then immersing it in a sodium salt solution, and drying it for the second time. More preferably, the solvent of the liquid containing the ion conductive agent comprises one or more of acetone and DMF. More preferably, the liquid containing the ion conductive agent further comprises 3 to 300 mg / mL of an organic filler, wherein the organic filler comprises polyvinylidene fluoride (PVDF). More preferably, the concentration of the ion conductive agent in the liquid containing the ion conductive agent is 1 to 100 mg / mL. More preferably, the concentration of the sodium salt solution is 0.05 to 10 mol / L. More preferably, the sodium salt comprises one or more of sodium hexafluorophosphate (NaPF6), sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bis(oxalatoborate), sodium bis(fluorosulfonyl)imide, and sodium trifluoromethanesulfonate.
[0063] According to another aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, and an electrolyte membrane as described above in any one of the present application, wherein the positive electrode sheet comprises a sodium ion transition metal oxide.
[0064] For example, the sodium ion transition metal oxide includes a molecular formula of NaNi x Fe y Co z Mn a M b Sodium composite oxide of O2, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤a≤1, 0≤b≤0.1, x+y+z+a+b=1, and M is selected from one or more of Fe, Zn, Ge, Ti, Zr, Mg, Al, Mo, and Sn.
[0065] According to another aspect of the present application, an electric device is provided, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.
[0066] Electric equipment refers to any device that can utilize electrical energy and convert it into one or more other forms of energy, such as mechanical energy, thermal energy, or light energy, including electric motors, electric heat generators, and electric light sources. Specifically, these devices include, but are not limited to, mobile devices, electric vehicles, electric trains, ships, satellites, and energy storage systems. Mobile devices include mobile phones, laptops, drones, robot vacuums, and electronic cigarettes. Electric vehicles include pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, and electric trucks.
[0067] Example 1
[0068] This embodiment provides an electrolyte membrane. Figure 1As shown, it includes a polymer film 23, an ion conductor 21, an organic solvent, an organic filler 22 and a sodium salt, wherein the ion conductor includes a NASCON ion conductor (Na3Zr2Si2PO 12 ) and halide ion conductor (Na3YbCl6), the mass ratio m1 / m2 of NASCON ion conductor to halide ion conductor and the particle size Dv50 of the two ion conductors are shown in Table 1.
[0069] The preparation method is as follows:
[0070] (1) Preparation of polymer membrane: PVDF-HFP was dissolved in DMF to prepare an electrospinning solution with an organic content of 13 wt%. After spinning for 60 min at a flow rate of 1 mL / h at 20 kV, polymer fibers were collected on a flat plate to form a film. The removed fibers were placed in a muffle furnace and heated at 185°C for 3 h to form a polymer membrane. The porosity, thickness, and tensile strength of the polymer membrane are shown in Table 2.
[0071] (2) Preparation of polymer composite membrane: Acetone and DMF were mixed in a volume ratio of 1:5 to form a mixed solution, 0.52 g of organic filler PVDF (weight average molecular weight Mw is 150000) and 0.09 g of NASCON ion conductor Na3Zr2Si2PO 12 and 0.09 g of halide ion conductor Na3YbCl6, added to 30 mL of the mixed solution and stirred evenly to form an ion conductor precursor solution, 20 mL of the above precursor solution was poured into a flat-bottomed glass dish with a diameter of 10 cm, and the polymer film with a thickness of 10 μm and an area of 5 cm × 5 cm prepared in step (1) was immersed therein, and the precursor solution was taken out after being completely absorbed (no liquid residue was observed in the glass dish), and finally dried at 45 ° C for 15 min to form a polymer composite membrane.
[0072] (3) Preparation of the Electrolyte Membrane: A sodium salt solution was prepared by dissolving NaPF6 in a propylene carbonate (PC) solvent to a sodium salt concentration of 0.5 mol / L. The polymer composite membrane was then immersed in the sodium salt solution. After 24 hours, the membrane was removed and dried at 45°C for 30 minutes to evaporate any residual liquid, resulting in the electrolyte membrane. The porosity, thickness, and ionic conductivity of the electrolyte membrane are shown in Table 2.
[0073] This embodiment also provides a secondary battery, comprising a positive electrode sheet 1, a negative electrode sheet 3, and an electrolyte membrane 2 located between the positive electrode sheet 1 and the negative electrode sheet 3, the preparation method of which is as follows:
[0074] Preparation of positive electrode sheet: O3 type layered oxide positive electrode material NaNi 0.32 Fe 0.32 Mn 0.33Zn 0.03 O2, conductive agent carbon black, and binder PVDF were mixed evenly in a mass ratio of 8:1:1, and then an appropriate amount of NMP was added to stir into a slurry. The slurry was coated on a 12 μm thick aluminum foil. After drying and cutting, a positive electrode sheet with a diameter of 12 mm was obtained. The active material surface density was 5 mg / cm 2 .
[0075] Button cell assembly: The positive electrode, the negative electrode metal sodium foil, the electrolyte membrane prepared above and the electrolyte (prepared by dissolving NaPF6 in a mixture of EC, PC and DMC, with a NaPF6 concentration of 1 mol / L and a volume ratio of EC, PC and DMC of 0.5:0.3:0.2) were assembled into a button cell, wherein the electrolyte was added in an amount of 5 μL to wet the interface between the electrode and the electrolyte membrane.
[0076] Examples 2-3
[0077] The preparation process is basically the same as that of Example 1, using the same batch and area of polymer membrane as in Example 1. The difference is that in step (2), different types of NASCON ion conductors or halide ion conductors are used to prepare different gel electrolytes and secondary batteries, as shown in Table 1.
[0078] Examples 4 to 6
[0079] The preparation process was essentially the same as in Example 1, using polymer membranes of the same area and batch as in Example 1. The difference was that the particle sizes Dv50 of the NASCON ion conductors or halide ion conductors were different to produce different gel electrolytes and secondary batteries, as shown in Table 1.
[0080] Examples 7-8
[0081] The preparation process is basically the same as that of Example 1, and the polymer membrane of the same area and the same batch as that of Example 1 is used. The difference is that the mass of the halide ion conductor and the NASCON ion conductor added to the mixed solution in step (2) is different. Specifically, in Example 7, the NASCON ion conductor Na3Zr2Si2PO 12 The mass of the halide ion conductor Na3YbCl6 is adjusted to 0.108g, the mass of the halide ion conductor Na3YbCl6 is adjusted to 0.072g, and the NASCON ion conductor Na3Zr2Si2PO 12 The mass of the halide ion conductor is adjusted to 0.072 g, and the mass of the halide ion conductor Na3YbCl6 is adjusted to 0.108 g, resulting in the total mass of the NASCON ion conductor and the halide ion conductor being unchanged but the mass ratio being different, so as to prepare different gel electrolytes and secondary batteries, as shown in Table 1.
[0082] Examples 9 to 11
[0083] The preparation process was essentially the same as that of Example 1, using a polymer membrane of the same area and the same batch as in Example 1. The difference was that the total mass of the NASCON ion conductor and the halide ion conductor added to the mixed solution in step (2) was adjusted to 0.0018 g, 0.36 g, and 0.64 g, respectively, and the mass ratio of the two ion conductors remained unchanged, resulting in different mass proportions of the ion conductor in the electrolyte membrane, thereby preparing different gel electrolytes and secondary batteries, as shown in Table 1.
[0084] Examples 12-13
[0085] The preparation process is basically the same as that of Example 1, and the same batch of polymer membranes as in Example 1 is used. The difference is that 0.06g of sulfide ion conductor is added to the mixed solution in step (2), and NASCON ion conductor Na3Zr2Si2PO 12 The mass of the halide ion conductor is adjusted to 0.06 g, and the mass of the halide ion conductor Na3YbCl6 is adjusted to 0.06 g. The types of sulfide ion conductors in these embodiments are different to prepare different gel electrolytes and secondary batteries. The mass ratio m1 / m3 of the NASCON ion conductor to the sulfide ion conductor and the particle size Dv50 of the sulfide ion conductor are shown in Table 1.
[0086] Example 14
[0087] The preparation process is basically the same as that of Example 12, and the polymer membrane of the same batch as that of Example 1 is used. The difference is that the amount of sulfide ion conductor is adjusted to make the mass ratio of NASCON ion conductor to sulfide ion conductor different. Specifically, NASCON ion conductor Na3Zr2Si2PO 12 The mass of the halide ion conductor Na3YbCl6 was adjusted to 0.03g, the mass of the sulfide ion conductor Na 11 Sn2PS 12 The mass of the electrolyte was adjusted to 0.12 g, and different gel electrolytes and secondary batteries were prepared, as shown in Table 1.
[0088] Examples 15 to 17
[0089] The preparation process is basically the same as that of Example 1, except that the electrospinning time is adjusted to 0.5 h, 2 h, and 5 h, so that the thickness of the polymer film is different, so as to prepare different gel electrolytes and secondary batteries, as shown in Table 1.
[0090] Examples 18 to 20
[0091] The preparation process is basically the same as that of Example 1, except that the concentration of the electrospinning solution is adjusted to 7wt%, 16wt%, and 20wt% to make the porosity of the polymer film different, so as to prepare different gel electrolytes and secondary batteries, as shown in Table 2.
[0092] Examples 21-22
[0093] The preparation process was basically the same as that of Example 1, and the same batch of polymer membranes was used. The difference was that the types of sodium salt and organic solvent were different to prepare different gel electrolytes and secondary batteries, as shown in Table 1.
[0094] Examples 23-24
[0095] The preparation process was essentially the same as that of Example 1, using the same batch of polymer membranes as in Example 1. The difference was that the sodium salt concentration in step (3) was adjusted to 0.125 mol / L and 1.875 mol / L, so that the mass proportion of the sodium salt in the electrolyte membrane was different, thereby preparing different gel electrolytes and secondary batteries, as shown in Table 1.
[0096] Examples 25-26
[0097] The preparation process was essentially the same as that of Example 1, using the same batch of polymer membranes as in Example 1. The difference was that the drying time at 45° C. in step (3) was adjusted to 60 min and 5 min, respectively, to achieve different mass proportions of the organic solvent in the electrolyte membrane, thereby preparing different gel electrolytes and secondary batteries, as shown in Table 1.
[0098] Comparative Examples 1 to 3
[0099] The preparation process is basically the same as that of Example 1, and the same batch of polymer membranes as in Example 1 is used. The difference is that no NASCON ion conductor and / or halide ion conductor is added in step (2), so as to prepare different gel electrolytes and secondary batteries, as shown in Table 1.
[0100] Comparative Examples 4-5
[0101] The preparation process was essentially the same as that of Example 1, using the same batch of polymer membranes as in Example 1. The difference was that the masses of the halide ion conductor and the NASCON ion conductor added to the mixed solution in step (2) were different, resulting in a constant total mass of the NASCON ion conductor and the halide ion conductor but different mass ratios, thereby preparing different gel electrolytes and secondary batteries, as shown in Table 1.
[0102] Table 1 Type, particle size, mass ratio and mass proportion of ion conductive agents
[0103]
[0104]
[0105] Table 2 Parameters of polymer membrane, sodium salt, organic solvent, organic filler and electrolyte membrane
[0106]
[0107]
[0108]
[0109] 1. Determination methods of physical parameters mentioned in the table:
[0110] 1) m1 / m2 and m1 / m3
[0111] The testing method is as follows: After disassembling the battery cell, remove the electrolyte membrane, soak it in an organic solvent such as DMC, wash away the residual sodium salt, and then dry it to evaporate the solvent. Then soak the obtained polymer composite membrane in an acetone solution to remove the organic filler and the polymer membrane. After washing and drying, the remaining insoluble ion conductor particle mixture can be obtained. The ion conductor mixture can be tested by ICP to obtain the precise value of the metal element, and the precise value of the metal element can be reversely calculated from the proportion of each ion conductor.
[0112] 2) Mass ratio of ion conductor in electrolyte membrane
[0113] The test method is as follows: weigh an electrolyte membrane with a mass of A1 and dissolve it in acetone, filter and wash to obtain a solid powder residue, and after drying, weigh the solid powder residue with a mass of B1. The mass proportion of the ion conductor in the electrolyte membrane is (A1 / B1)×100%.
[0114] 3) Mass ratio of sodium salt in the electrolyte membrane
[0115] The test method is as follows: During the production of the electrolyte membrane, first record the mass of the polymer composite membrane per unit area as A2, then record the mass of the corresponding electrolyte membrane per unit area as B2, and vacuum dry the electrolyte membrane per unit area at 80°C for 24 hours to obtain a dry electrolyte membrane with a mass of C1. Then the mass proportion of sodium salt in the electrolyte membrane is (C1-A2) / B2×100%.
[0116] 4) Mass ratio of organic solvent in electrolyte membrane
[0117] The test method is as follows: weigh an electrolyte membrane with a mass of A3, vacuum dry it at 80°C for 24 hours, and obtain a dry electrolyte membrane with a mass of C3. The mass proportion of the organic solvent in the electrolyte membrane is (A3-C3) / A3×100%.
[0118] 5) Thickness of polymer membrane and electrolyte membrane
[0119] The measurement method is as follows: in a 3cm×3cm square area, divide it into a 1cm×1cm "9-square grid" area, use a micrometer to measure the thickness of the center point of each area, and take the average value to obtain the thickness of the polymer membrane and the electrolyte membrane.
[0120] 6) Porosity of polymer membrane and electrolyte membrane
[0121] The determination method is as follows: After disassembling the battery cell, remove the electrolyte membrane, soak it in an organic solvent such as DMC, wash it, and vacuum dry it to remove the organic solvent to obtain a polymer composite membrane. Then, test the porosity of the polymer membrane according to GB / T 33052-2016.
[0122] 7) Tensile strength of polymer films
[0123] The measurement method is as follows: After disassembling the battery cell, remove the electrolyte membrane, soak it in an organic solvent such as DMC, wash it, and vacuum dry it to remove the organic solvent to obtain a polymer composite membrane. Then, use a universal tensile testing machine to test the tensile strength of the polymer membrane in accordance with GB / T 1040.3-2006.
[0124] 8) Ionic conductivity of the electrolyte membrane
[0125] The measurement method is as follows: after the battery cell is disassembled, the electrolyte membrane is taken out, and a metal sodium foil is used as a symmetrical electrode. The electrolyte membrane and sodium foil with a thickness of L and an area of S are made into a CR2032 type symmetrical button battery. The AC impedance at 25°C is measured to be R, and the ionic conductivity σ = (R×S) / L.
[0126] 2. The battery testing method is as follows:
[0127] 1) Battery rate performance test: The rate performance tests were conducted at room temperature (25°C) and low temperature (-10°C), with the theoretical gram capacity of the positive electrode as the current value at a rate of 1C. The reversible specific capacity of the battery was tested at room temperature and low temperature using 0.5C, 2C, and 5C rates, respectively.
[0128] 2) Battery cycle performance test: At an ambient temperature of 25°C, let it stand for 5 minutes, charge at a constant current rate of 1C to 4.05V, then charge at a constant voltage to a current equal to 0.05C, let it stand for 5 minutes, and then discharge at a constant current rate of 1C to 2.0V to complete one cycle. The button battery was subjected to 300 cycles of charge and discharge tests according to the above method, and the discharge capacity in grams after each cycle was recorded. Capacity retention rate after 300 cycles (%) = discharge capacity in grams at the 300th cycle / discharge capacity in grams after the first cycle × 100%.
[0129] The test results are shown in Table 3:
[0130] Table 3 Battery rate performance and cycle performance test results
[0131]
[0132]
[0133] It can be seen from the above table that, compared with Comparative Examples 1 to 5, the electrolyte membrane of the present application can not only significantly improve the battery cycle stability, but also significantly improve the room temperature and low temperature rate performance of the battery.
[0134] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will appreciate that other variations or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of this application.
Claims
1. An electrolyte membrane, characterized in that The invention comprises a polymer membrane, an ion conductive agent, an organic solvent, an organic filler and a sodium salt, wherein the polymer membrane has pores, and the ion conductive agent, the organic solvent, the organic filler and the sodium salt are distributed in at least a portion of the pores; the ion conductive agent comprises a NASCON ion conductor and a halide ion conductor; The ion conductor satisfies the following relationship: 0.2≤m1 / m2≤1.5; wherein m1 is the mass of the NASCON ion conductor in the electrolyte membrane, and m2 is the mass of the halide ion conductor in the electrolyte membrane.
2. The electrolyte membrane according to claim 1, wherein The NASCON ion conductor comprises at least one of the compounds of the following chemical formula: Na 1+x Zr 2-y M y Si x-y P 3-x+y O 12 , wherein 0≤x≤3, 0≤y≤1, and M is selected from one or more of Li, Ca, Mg, Sr, Ba, In, Ga, Nb, La, Cr, Mn, Zn, Al, Ge, and Bi; The chemical formula of the halide ion conductor is as follows: Na3NX6, wherein N is selected from one or more of Sc, Y, Yb, and In, and X is a halogen.
3. The electrolyte membrane according to claim 1, wherein The ion conductor also includes a sulfide ion conductor, which includes Na3Sn2S4, Na3W2S4, Na3Sb2S4, Na 11 Sn2SbS 12 、Na 11 Sn2PS 12 One or more of .
4. The electrolyte membrane according to claim 3, characterized in that The ion conductor satisfies the following relationship: 0.2≤m1 / m3≤1; wherein m3 is the mass of the sulfide ion conductor in the electrolyte membrane.
5. The electrolyte membrane according to claim 1, wherein The sodium salt includes one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium trifluoromethanesulfonate (NaSO3CF3), sodium bis(trifluoromethanesulfonyl)imide (NaN(CF3SO2)2), sodium tris(trifluoromethanesulfonyl)methyl (NaC(CF3SO2)3), sodium bis(oxalatoborate) (NaBOB), sodium difluorooxalatoborate (NaODFB), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and sodium difluorophosphate (NaPO2F2); and / or, The organic solvent includes one or more of ethyl methyl carbonate, ethylene carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, γ-butyrolactone, ethyl difluoroacetate, dimethyl carbonate, methyl propionate, methyl trifluoroacetate, ethyl propionate, propyl propionate, tetrahydrofuran, 2-methyltetrahydrofuran, ethyl acetate, propyl acetate, difluoroethyl acetate, ethyl trifluoroacetate, and propyl trifluoroacetate; and / or the organic filler includes one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and derivatives thereof.
6. The electrolyte membrane according to claim 1, wherein At least one of the following conditions is met: a. The mass proportion of the ion conductive agent in the electrolyte membrane is 0.5%-20%; b. The mass percentage of the sodium salt in the electrolyte membrane is 2% to 16%; c. The mass proportion of the organic solvent in the electrolyte membrane is 5% to 45%; d. The particle size Dv50 of the ion conductive agent is 0.5 to 30 μm; e. The organic filler accounts for 35-56% by mass in the electrolyte membrane.
7. The electrolyte membrane according to claim 1, wherein At least one of the following conditions is met: 1) The thickness of the polymer film is 5 to 50 μm; 2) The tensile strength of the polymer film is 48 to 72 MPa; 3) The porosity of the polymer film is 15% to 60%.
8. The electrolyte membrane according to claim 1, wherein At least one of the following conditions is met: A. The porosity of the electrolyte membrane is 15% to 70%; B. The thickness of the electrolyte membrane is 7 to 55 μm; C. The room temperature ionic conductivity of the electrolyte membrane is 2.6×10 -3 ~4.6×10 -3 S / cm.
9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, and the electrolyte membrane according to any one of claims 1 to 8, wherein the positive electrode sheet comprises a sodium ion transition metal oxide.
10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery serves as a power supply for the electrical device.